Bedknobs and broomsticks [videorecording (DVD)] - Stevenson, Robert, 1905-1986; Lansbury, Angela, 1925-; Tomlinson, David, 1917-2000; Jaffe, Sam, 1891-1984; Norton, Mary (Walt Disney Studios Home Entertainment, 2009)
An amateur witch, along with three precocious orphans, flies into one fantastic adventure after another aboard a bewitched bed to save the country from hostile invaders.